Determinants of industrial development in Central European countries: Empirical evidence from a dynamic panel analysis - Aderemi, Timothy A (Asian Economic and Financial Review, 2025)
This study investigated the determinants of industrial development in ten (10) Central European countries from 1990 to 2021. We used a panel ARDL method to study the effects of key economic factors on industrial growth to achieve this goal. These factors included credit to the private sector, market size, internet access, and trade openness. The results showed the following: Firstly, trade openness had a positive and significant effect on industrial development in Central Europe. This evidence implies that trade openness is a major factor that drives industrial development forward. However, market size and internet accessibility had a negative and significant effect on industrial development in Central Europe. This finding implies that the major economic factors that drive industrial development backward in Central Europe are market size and internet accessibility. Therefore, this study recommends that since trade openness is the major economic factor that propels industrial development forward in Central Europe, policymakers in this economic bloc should embark on a dynamic trade policy that will integrate Central Europe with other emerging markets. Furthermore, the practical implication is that policymakers in Central Europe should embark on policies that expand their domestic market by encouraging their citizens to patronize locally manufactured products.